Simultaneous Spectrophotometric Estimation of Amlodipine and Enalapril in Tablets Using Orthogonal Polynomial Function Method - Kannappan, N.; Kannan, K.; Manavalan, R. (Asian Journal of Chemistry, 2010)
Orthogonal polynomial function method has been developed for the simultaneous estimation of binary mixtures of amlodipine and enalapril in tablet formulations. All the parameters for orthogonal polynomial function method have been optimized by using computer programme in “C” language. The method was applied for the determination of these combinations in synthetic mixtures and tablet dosage forms. The contents of amlodipine in tablets were found to be 5.05 mg and of enalapril 5.03 mg of the label claim (5 mg of amlodipine and 5 mg of enalapril), respectively. The linearity was validated by least square method. The recovery is within the limits of 98-102%. The proposed methods are simple, economical, accurate, reproducible and rapid.